(untitled) (Prosiding Konseling Kearifan Nusantara (KKN), 2024)
This research aims to examine the implementation of Ki Hadjar Dewantara’s "Asah Asih Asuh" (A3) value in supporting educational services and its contribution to guidance and counseling (BK) supervision services. The method used in this research is a literature study that includes literacy analysis of the implementation of A3 values and BK supervision services. Data analysis was conducted by organizing, synthesizing, and interpreting the value of A3 in the context of education and BK supervision. The search results show that the A3 value is proven to optimize the educational process in various scientific fields, can be carried out at various levels of education, can be implemented in all educational leaders and is not culturally biased. The results of the review show that the A3 value has a high relevance to the principles of supervisors. Future recommendations need to apply the A3 value in BK supervision services to optimize culturally appropriate supervision.